Cangkok Tulang Gigi Anterior Maksila Pada Pasien Periodontitis Kronis Dengan Polisitemia Vera (Laporan Kasus) - Muhammad Yusuf; Shinta Ferronika (FKG Universitas Syiah Kuala, 2024)
Introduction: Polycythemia vera is a myeloproliferative disorder characterized by myeloid proliferation and causes increased erythrocyte production. This condition is a challenge for patients with periodontitis. Periodontitis accompanied by occlusion trauma can cause bone loss, recession and tooth mobility. Aim: This case report describes the management of a patient with polycythemia vera in preserving teeth and restoring healthy periodontal tissue with flap surgery and bone grafting. Case: 43 year old male patient with complaints of loose upper front teeth for the past few years. Clinical examination showed grade 2 tooth luxation, accompanied by a periodontal pocket of 6 mm. Radiographic examination showed vertical bone loss in the anterior region of the maxilla. The patient has undergone initial treatment in the form of scaling, root planing, and splinting with fiber composite as well as occlusal adjustment. Coordination and clinical evaluation of the patient by a hemato-oncologist in preparation for flap surgery with bone graft application. Treatment: In cases of vertical bone loss accompanied by loose teeth due to occlusion trauma, adequate treatment is needed. Flap surgery is performed to eliminate deep pockets and bone grafts for bone regeneration. Conclusion: Coordinated efforts of hemato-oncologists and periodontists are necessary for periodontal treatment, especially invasive therapy. The reconstructive surgical procedure with bone graft in this case showed quite good results.Keywords: polycythemia vera; flap surgery; bone graft